RIBONUCLEIC ACID ISOLATION FROM HUMAN MONONUCLEAR CELL CULTURE WITH MAGNETIC BEADS PRE-ENRICHMENT FOR MOLECULAR ANALYSIS - Bhatia, Sudhir (Sanamed, 2024)
Introduction: In order to develop immunotherapies and therapeutic humoral molecules, ribonucleic acid (RNA) from cultured mononuclear cells (MNCs) is needed. However, it is not possible to isolate RNA using the standard mini column method from older MNC cultures. Therefore, the aim of this study was to develop a method to isolate RNA from MNC cultures, particularly older ones.Materials and Methods: MNC cultures were grown from human buffy coats. The media from the cell culture was centrifuged to generate a pellet, to which CD45-specific magnetic beads were added. RNA was then isolated using the mini column method. The housekeeping gene beta-actin was used to confirm the success of RNA isolation through both real-time and conventional PCR tests.Results: RNA was successfully isolated from MNC cultures, especially those that were a few months old, after pre-enrichment with magnetic beads. Without the magnetic bead pre-enrichment step, RNA isolation was not achieved. The results of the housekeeping gene tests indicated successful RNA isolation in all cases through both real-time and conventional PCR. Additionally, spectrophotometric values of the isolated RNA confirmed successful isolation.Conclusion: This study is the first to demonstrate that it is possible to isolate RNA from human MNC cultures, particularly older ones, using specific magnetic beads. This method opens new opportunities for conducting genetic analyses, biomarker confirmation, and the development of antibodies.
Keywords: Mononuclear cells; RNA isolation; Mini column method; Polymerase chain reaction